Anterior Cruciate Ligament Injuries in Pediatric Athletes Presenting to Sports Medicine Clinic: A Comparison of Males and Females Through Growth and Development. (March 2015) - Stracciolini, Andrea; Stein, Cynthia J.; Zurakowski, David; Meehan, William P.; Myer, Gregory D.; Micheli, Lyle J.
Background: Limited data exist regarding the effect of the growth process on anterior cruciate ligament (ACL) injury risk in male versus female children. Hypothesis: The proportion of ACL injuries/sports injuries presenting to clinic will vary by age, sex, and body mass index (BMI). Study Design: Cross-sectional epidemiologic study. Level of Evidence: Level 3. Methods: The study group consisted of a randomly selected 5% probability sample of all children 5 to 17 years of age presenting to a sports medicine clinic from January 1, 2000 to December 31, 2009; 2133 charts were reviewed. Data collected included demographics, height and weight, injury mechanism, diagnosis, treatment, previous injury, and organized sports. Results: A total of 206 ACL tears were analyzed (104 girls, 102 boys). Girls were slightly older than boys (15.1 ± 1.7 vs 14.3 ± 2.1 years; P < 0.01). Male-female comparison of ACL injury/total injury by age revealed that girls had a steeper increase by age than boys. Among 5- to 12-year-olds, boys had a higher ACL injury/total injury ratio than girls (all P < 0.01). Children 13 to 17 years of age showed no significant difference for sex in ACL injury/total injury ratio. As age advanced, the proportion of ACL injuries/total injuries increased for both girls ( P < 0.01) and boys ( P = 0.04). BMI was independently associated with an ACL injury ( P < 0.01). Conclusion: The proportion of ACL injuries/total injuries was similar for boys and girls aged 13 to 17 years. Girls showed a significantly steeper increase in ACL injury proportion versus boys through puberty. Clinical Relevance: This study will increase clinician awareness of ACL injury occurrence in young male and female athletes 5 to 12 years of age. Injury prevention efforts should target young girls before the onset of puberty and before injury occurs.